Cardiovascular risk assessed by the conicity index in Brazilian adults: findings from the national health survey - Silva, Yasmin Franco Rodrigues; do Prado, Camila Bruneli; Muniz, Virgínia Maria; Haraguchi, Fabiano Kenji; Salaroli, Luciane Bresciani (Frontiers in Nutrition, 2026)
BackgroundAnthropometric indices such as the Conicity Index (C-Index) are emerging as accessible tools to assess cardiovascular risk associated with central adiposity, a key determinant of cardiovascular disease burden in low and middle-income countries.AimTo estimate the prevalence of cardiovascular risk using the CI and examine its association with sociodemographic and lifestyle factors in a nationally representative sample of Brazilian adults.MethodsIn this cross-sectional study using data from the 2013 Brazilian National Health Survey (n = 42,693; ages 30–74), cardiovascular risk was defined based on sex-specific CI cut-off points.ResultsThe overall prevalence of elevated cardiovascular risk was 39.6%, with a significantly higher rate among women (64.6%) compared to men (35.4%). Increased age, lower education, lower income, poor self-rated health, and physical inactivity were independently associated with greater cardiovascular risk, with regional and sex-based differences observed.ConclusionThe CI proved to be a practical, non-invasive measure strongly associated with key social determinants of health and behavioral risk factors. These findings support its integration into public health monitoring and preventive strategies to identify at-risk groups, particularly in resource-constrained settings.